A low surface tension long-lasting developer

The developer is prepared by electrolyzing TMAH aqueous solution of composite anode electrode, and the problems of insufficient surface tension and poor stability of semiconductor-grade TMAH developer are solved, and the development effect and production of photoresist are achieved. efficiency.

CN118668231BActive Publication Date: 2025-02-11HANGZHOU GREENDA CHEM +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410879528.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-02-11
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

The existing semiconductor-grade TMAH developer has problems of insufficient surface tension and poor stability in the manufacturing of high-fine large-scale integrated circuits, which affects the development effect and production efficiency of photoresist.

Method used

The composite anode electrode is used to prepare a low-surface tension long-term developer by electrolyzing TMAH aqueous solution. The titanium dioxide layer and mixed oxide layer with grid structure are formed to improve the Conductivity and adhesion properties of the electrode.

Benefits of technology

The low surface tension and long-term stability of the developer are achieved, the development effect and production efficiency of the photoresist are improved, the metal ion content is reduced, and the alkali retention force and wide temperature performance are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118668231B_ABST
    Figure CN118668231B_ABST
Patent Text Reader

Abstract

The present invention discloses a low surface tension long-acting developer. The low surface tension long-acting developer of the present invention is prepared by using a composite anode electrode prepared by the present invention to electrolyze a TMAH aqueous solution at the cathode, in combination with an alkaline substance, an alcohol or ether substance, and a surfactant. The preparation process of the electrode includes: forming a titanium dioxide layer with a nano-grid morphology on the surface of a titanium substrate by an in-situ synthesis method, and then obtaining a composite anode electrode containing a first composite layer and a second composite layer of active components such as tin, tantalum, and titanium by an impregnation, drying, and roasting cycle deposition method. The in-situ synthesis method constructs a nano-grid morphology, which is conducive to the deposition of active components such as tin, tantalum, and titanium, and improves the activity of the active components; the specific morphology and cyclic deposition method improve the strength, adhesion, conductivity, durability, etc. of the composite electrode film. The developer of the present invention has comprehensive properties such as improved alkalinity retention, surface tension, and wide temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent with application number: 202311144197.1, application date: September 6, 2023, and invention name: "A method for preparing a low surface tension long-lasting developer". Technical Field

[0002] The present invention relates to the technical field of photolithography and development, in particular to the preparation of a composite anode electrode for TMAH electrolysis, and a low-surface-tension long-acting developer prepared by using the electrode to electrolyze a TMAH aqueous solution as a developer component, and to the application of the composite anode electrode in the preparation of liquid crystal displays, printed circuit boards and integrated circuits. Background Art

[0003] Developer is mainly used in the photolithography process. The photolithography process is a process that uses exposure, development and etching to transfer the pattern on the photomask to the substrate material. It is an important step in the manufacturing process of integrated circuit devices. The photolithography process has developed from G-line, I-line, KrF to the most advanced ArF and EUV today. Its progress is inseparable from the continuous development of photoresists and supporting developer reagents. Developer is a category with a large demand in the field of wet electronic chemicals for integrated circuits. With the requirements for high-end integrated circuits, the use of high-performance developers is more important.

[0004] Developers are mainly used in the manufacturing process of chips, high-resolution flat panel displays, and OLED flexible displays. As the application fields become more sophisticated and emerging technologies are rapidly updated and iterated, the development of semiconductor-grade TMAH developers is more important. They are suitable for the positive photoresist development step in the graphic process of the high-precision large-scale integrated circuit manufacturing industry.

[0005] The research on semiconductor-grade TMAH developer has been continuously improving and developing, and the preparation and purification process of TMAH has always been the focus of the industry. In the electronics industry, the quality indicators of TMAH products mainly include the content of particulate impurities, metal ions and anionic impurities, which are strictly controlled according to specific applications. The methods for preparing tetramethylammonium hydroxide are mainly divided into: (1) silver oxide method; (2) ion exchange resin method; (3) alkali replacement method; (4) membrane electrolysis method; (5) bipolar membrane electrodialysis method. Among them, the silver oxide method has the disadvantages of high cost and the product is easily contaminated by silver ions. The product obtained by the ion exchange resin method is not of high purity and the resin is difficult to regenerate. The alkali replacement method is also easy to mix with impurity ions during the production process. Compared with the other three methods, membrane electrolysis and bipolar membrane electrodialysis have the advantages of low cost and high product purity. Therefore, membrane electrolysis and bipolar membrane electrodialysis have become the focus of research by domestic and foreign researchers.

[0006] In addition, as the storage capacity of ICs gradually increases, the storage capacity of memory batteries needs to be increased as much as possible, so the oxide film becomes thinner. Alkali metal impurities (Na, Ca, etc.) in wet chemicals will dissolve into the oxide film, resulting in a decrease in insulation withstand voltage. If heavy metal impurities (Cu, Fe, Cr, Ag, etc.) in wet electronic chemicals adhere to the surface of silicon wafers, the withstand voltage of the PN junction will be reduced. The adhesion of impurity molecules or ions is the main cause of chemical failures such as corrosion or leakage. Therefore, with the rapid development of microelectronics technology, the higher the line width of large-scale integrated circuits, the higher the requirements for wet electronic chemicals. The content requirements of metal and non-metal impurities and particles in different levels of wet chemicals are different, so they are matched with integrated circuit process technologies of different line widths, that is, a generation of integrated circuit products requires a generation of ultra-clean high-purity reagents to match them.

[0007] In some advanced semiconductor manufacturing processes, a certain amount of surfactant that meets the purity requirements of the application is required to be added to the high-purity developer for photoresist, so that the surface tension of the developer is reduced, so that it can fully contact and infiltrate the photoresist, reduce the defects of insufficient photoresist development, meet the client's requirements for key parameters in the development process, and improve the production yield of the final chip product. At the same time, the mixing speed needs to be increased during the mixing process to improve the production efficiency of the high-purity developer for photoresist.

[0008] At present, the mainstream products of my country's chip industry are concentrated in the middle and low-end industry. The current situation is still grim. The development of display and integrated circuit technology such as flexible OLED still lags behind that of European, American, Japanese and Korean companies. The main reason is that the industry's technical barriers are extremely high. Semiconductor integrated circuit manufacturing requires wet electronic chemicals to reach SEMI G4 and above, especially the high-precision graphic process (photolithography process) is extremely difficult. At the same time, key materials such as wet electronic chemicals have long been mainly dependent on imports. The resulting import trade deficit and dependence on foreign technology have seriously hindered the development of the integrated circuit industry. Among them, the developer used in the integrated circuit field, domestic developer manufacturers still have a certain gap in product technology level with international leading companies. Its market is mainly occupied by top foreign wet electronic chemical companies such as Sankai Chemical Company of the United States and Tokyo Ohka Industry Co., Ltd. If domestic local enterprises can achieve independent research and development and industrial application of high-purity developer supporting photoresist for key semiconductor materials in the field of large-scale integrated circuits, it can not only use this as a breakthrough to promote import substitution and fully reduce the production costs of domestic chip manufacturers, but also break the foreign technology monopoly, solve the problem of localization of key "stuck neck" materials in the field of integrated circuits, and promote the healthy development of the entire industrial chain.

[0009] In 2021, the overall localization rate of wet electronic chemicals for integrated circuits in my country reached 35%. However, the compound wet electronic chemicals used in advanced technology nodes below 28nm for 12-inch wafers of integrated circuits are materials that my country is currently subject to control and are basically dependent on imports. Core technical difficulties urgently need to be overcome as soon as possible.

[0010] Chinese patent CN103197516A uses a developer prepared by combining TMAH and TEAH in a certain proportion to significantly improve the development quality, reduce the risk of pattern collapse, and effectively improve the development stability and improve the development efficiency.

[0011] Chinese patent CN114859677A discloses a tetramethylammonium hydroxide developer, a preparation method and an application thereof. The patent adopts a tetramethylammonium hydroxide developer, polyoxyethyl glycerol ether, ammonium citrate and water, and the mass ratio of polyoxyethyl glycerol ether to ammonium citrate is 1:1-10 to obtain a tetramethylammonium hydroxide developer. During the etching process, the developer can have excellent development results, less residue and good storage stability, and is suitable for use in the preparation of liquid crystal displays, printed circuit boards and integrated circuits.

[0012] However, with the advancement of high-end technology, the pursuit of high-performance developers has always been a long-term expectation of developers. Summary of the invention

[0013] In view of the deficiencies of the prior art, the present invention provides a method for preparing a composite anode electrode for semiconductor-grade TMAH electrolysis and a low-surface-tension long-acting developer prepared by electrolyzing an aqueous solution using the composite anode electrode.

[0014] In one embodiment of the present invention, a method for preparing a semiconductor-grade composite anode electrode for TMAH electrolysis is provided, comprising the following steps:

[0015] 1. Pretreatment of titanium substrate: A commercially available titanium substrate of length 8 cm × width 4 cm × thickness 2.0 mm was degreased and deoiled using alkali solution, acetone and acid solution in sequence.

[0016] 2. Surface modification of titanium substrate: A titanium dioxide layer with a grid morphology is prepared on the surface of the titanium substrate by an in-situ synthesis method using an anhydrous ethanol solution of titanium trichloride and urea and a hydrothermal reaction in the presence of a small amount of water.

[0017] 3. Preparation of composite anode electrode:

[0018] First layer composite: prepare an aqueous solution of Sn chloride (SnCl4) containing 5-20g / 100ml Sn and an aqueous solution of Ti chloride (TiCl 3) containing 5-20g / 100ml, take 100ml of each of the aqueous solutions and add ethanol to form a 300ml first mixed solution; immerse the titanium substrate modified in step 2 in the obtained first mixed solution for 0.5-2 hours, dry at 80-120°C for 10-30 minutes under atmospheric atmosphere, transfer to a muffle furnace and roast at 480-600°C for 30-240 minutes under atmospheric atmosphere; perform the above-mentioned immersion, drying and roasting processes in sequence until the first mixed solution is completely used up, and form a layer containing tin and titanium mixed oxides on the surface of the titanium substrate to obtain a titanium substrate anode electrode containing the first composite layer;

[0019] Second layer composite: prepare an aqueous solution containing 1-6g / 100ml of Ta chloride (TaCl 5) and an aqueous solution containing 5-20g / 100ml of Ti chloride (TiCl 3), take 100ml of each of the above aqueous solutions and add them to ethanol to form 300ml of a second mixed solution; immerse the titanium substrate anode electrode obtained after the first layer composite in the obtained second mixed solution for 0.5-2 hours, dry it at 80-120°C in an atmospheric atmosphere for 10-30 minutes, transfer it to a muffle furnace and roast it at 450-600°C in an atmospheric atmosphere for 30-240 minutes; carry out the above-mentioned immersion, drying and roasting processes in sequence until the second mixed solution is completely used up, and form a second layer containing tantalum and titanium mixed oxides on the surface of the titanium substrate to obtain a conductor-grade composite anode electrode for TMAH electrolysis. The composition of the titanium substrate surface coating layer formed is TiO2-SnO2-Ta2O5, and the metal content is 69.3% Ti, 27.9% Sn, and 2.8% Ta.

[0020] In the pretreatment process of the titanium substrate of the present invention, the specific treatment method is to soak it in a 1-4 mol / L sodium hydroxide solution at 25°C for 10-60 minutes and then treat it with acetone for 10-30 minutes to obtain a titanium substrate with oil and grease removed; then soak it in a 0.5-2 mol / L oxalic acid solution at 45°C for 30-90 minutes to obtain a titanium substrate with the oxide layer and grease removed.

[0021] In the surface modification process of the titanium substrate of the present invention, the specific method is to immerse the titanium substrate after removing the oxide layer and grease in 100 ml of anhydrous ethanol solution with a titanium trichloride concentration of 1-3 mol / L and a urea concentration of 0.5-3 mol / L, slowly drop 10-20 ml of deionized water within 20 minutes, stir evenly and transfer to a high-temperature and high-pressure reactor with a Teflon liner at 160-220° C. for hydrothermal reaction for 6-12 hours. After the reaction is completed, it is naturally cooled to room temperature, and the titanium substrate is washed with distilled water for several times; the titanium substrate with white powder on the surface is placed in a drying oven at 100-120° C. and dried for 2-4 hours to obtain a titanium substrate with surface modified with titanium dioxide.

[0022] In the preparation process of the composite anode electrode of the present invention, the concentration of the aqueous solution of tin chloride (SnCl4) of tin in the first composite layer is preferably 10-15g / 100ml, and the concentration of the aqueous solution of Ti chloride (TiCl 3) is preferably 10-15g / 100ml; the concentration of the aqueous solution of Ta chloride (TaCl 5) in the second composite layer is preferably 1-2g / 100ml, and the concentration of the aqueous solution of Ti chloride (TiCl 3) is preferably 10-15g / 100ml.

[0023] In one embodiment of the present invention, a semiconductor-grade TMAH electrolysis process is provided, and the electrolysis process of the present invention comprises: pretreatment of F4402 cation exchange membrane, before use, soaking it in a 0.2-1mol / L sulfuric acid deionized water solution for 6-8 hours, washing it with deionized water, and then soaking it in a 4wt% tetramethylammonium hydroxide solution for 24 hours, and washing it with deionized water for standby use. In a double-chamber single-membrane electrolytic cell, the composite titanium substrate obtained in the present invention is used as an anode, and a commercially available 304 stainless steel plate of 8cm×4cm×2.0mm is used as a cathode electrode, 500mL of a tetramethylammonium bicarbonate aqueous solution with a mass concentration of 10-30% is added to the anode chamber of the electrolytic cell, and 500mL of a tetramethylammonium hydroxide (TMAH) aqueous solution with a mass concentration of 1-2% is added to the cathode chamber; the electrolytic cell temperature is maintained at 45-60°C, the voltage is 8V, the current is 1.5A, and the electrolysis is performed for 12-24 hours to obtain a semiconductor-grade TMAH aqueous solution in the cathode chamber. Inductively coupled plasma mass spectrometry (ICP-MS) was used to detect the content of metal ions (K, Ca, Na, Mg) (in ppb).

[0024] An embodiment of the present invention provides a low surface tension long-acting developer; the developer of the present invention uses the semiconductor-grade TMAH aqueous solution obtained in the cathode chamber of the embodiment of the present invention as the developer composition.

[0025] The low surface tension long-acting developer of the present invention is further prepared by adding corresponding alkaline substances, surfactants, alcohol and ether derivatives, etc.

[0026] In the low surface tension long-acting developer of the present invention, the alkaline substance is selected from one or more of choline, alcohol amine, amide, and pyrrolidone, and the added amount is based on tetramethylammonium hydroxide (TMAH) aqueous solution, and the mass concentration is 0.5-3%.

[0027] In the low surface tension long-acting developer of the present invention, if the surfactant is a nonionic surfactant, polyoxyethylene alkyl ether, polyoxyethylene polyoxypropylene alkyl ether, polyoxyethylene alkyl phenyl ether, polyoxyalkylene polycyclic phenyl ether, polyoxypropylene polyoxyethylene polyoxypropylene alkyl ether, polyoxyethylene polyoxypropylene alkyl phenyl ether, polyethylene glycol, polyoxyethylene polyoxypropylene glycol, polypropylene glycol, polyoxyethylene polyoxypropylene polyoxyethylene glycol, polyoxyethylene fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene alkyl amide, polyoxyethylene polyoxypropylene alkyl amide, alkylamino polyoxyethylene ether, alkylamino polyoxyethylene polyoxypropylene ether, acetylene glycol polyoxyethylene ether, coconut amine polyoxyethylene ether, polyoxyethylene glycerol ether can be selected; the added amount is based on tetramethylammonium hydroxide (TMAH) aqueous solution, and the mass concentration is 0.5-5%.

[0028] The low surface tension long-acting developer of the present invention, the alcohol and ether derivatives are selected from pentaerythritol, neopentyl glycol, xylitol, n-butanol, maltitol, ethylene glycol ether, propylene glycol ether, the addition amount is based on tetramethylammonium hydroxide (TMAH) aqueous solution, and the mass concentration is 0.5-3%; the propylene glycol ether is selected from propylene glycol butyl ether and propylene glycol propyl ether.

[0029] The low surface tension long-acting developer of the present invention may also contain additives such as an anti-aging agent, a defoamer, and a corrosion inhibitor, with a content of 0.1-2%. The anti-aging agent is an amine or a phenol, the defoamer is one or more of silicone oils, and the corrosion inhibitor is one or more of benzotriazole and 5-methylbenzimidazole.

[0030] The present invention provides a method for preparing a low surface tension long-acting developer. 100 g of a tetramethylammonium hydroxide (TMAH) aqueous solution obtained by cathode electrolysis in one embodiment of the present invention is weighed, and corresponding alkaline substances, surfactants, alcohols and ether derivatives are added in sequence, and additives are optionally added, and the mixture is fully stirred and mixed.

[0031] In the preparation process of the semiconductor-grade TMAH electrolysis composite anode electrode of the present invention, a titanium dioxide powder with a grid structure is formed on the surface of a titanium substrate by an in-situ synthesis method, and then a composite anode electrode containing a first composite layer and a second composite layer is obtained by an impregnation, drying, and roasting cycle deposition method. The in-situ synthesis method constructs a grid-shaped structure, which is conducive to the deposition of active components such as tin, tantalum, and titanium, and increases the activity of the active components. The specific morphology and cyclic deposition method improve the strength, adhesion performance, conductivity, durability, etc. of the composite electrode film.

[0032] The low surface tension long-acting developer of the present invention adopts the low metal content aqueous solution electrolyzed at the cathode by the electrode obtained by the present invention, combined with alkaline substances such as choline, alcohol amine, alcohol or ether substances, and surfactants, thereby improving the alkalinity retention, surface tension and wide temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a scanning electron microscope photograph of the powder on the surface of the titanium substrate prepared in Example 1.

[0035] Figure 2 The XRD diffraction patterns of the titanium substrate surface powders prepared in Examples 1-3 and Comparative Example 1.

[0036] Figure 3 This is a scanning electron microscope photograph of the surface powder of the titanium substrate prepared in Comparative Example 1. DETAILED DESCRIPTION

[0037] The following examples are used to further illustrate the effects and functions of the method of the present invention. The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.

[0038] Example 1

[0039] Preparation of titanium substrate anode for electrolysis of tetramethylammonium hydroxide

[0040] 1. Pretreatment of titanium substrate: A commercially available titanium substrate of length 8 cm × width 4 cm × thickness 2.0 mm was immersed in a 2 mol / L sodium hydroxide solution at 25°C for 20 minutes and then treated with acetone for 10 minutes to obtain a titanium substrate from which oil and grease had been removed; then, the substrate was immersed in a 0.5 mol / L oxalic acid aqueous solution at 45°C for 90 minutes to obtain a titanium substrate from which the oxide layer and grease had been removed.

[0041] 2. Surface modification of titanium substrate:

[0042] The titanium substrate with the oxide layer and grease removed was immersed in 100 ml of anhydrous ethanol solution with a titanium trichloride concentration of 1 mol / L and a urea concentration of 1.5 mol / L. 20 ml of deionized water was slowly added within 20 minutes. After stirring evenly, it was transferred to a high-temperature and high-pressure reactor with a Teflon liner for hydrothermal reaction at 200°C for 12 hours. After the reaction was completed, it was naturally cooled to room temperature and the titanium substrate was washed with distilled water several times; the titanium substrate with white powder on the surface was placed in a drying oven at 120°C for 4 hours to obtain a titanium substrate with surface modified with titanium dioxide. A small amount of white powder on the surface was scraped for sample testing. The scanning electron microscope image is as follows Figure 1 The XRD diffraction spectrum is shown in Figure 2 As shown, the XRD diffraction peak shows that the obtained surface white powder is a titanium dioxide phase, and the scanning electron microscope image shows that the microstructure of the white powder is a grid-shaped structure.

[0043] 3. Preparation of composite anode electrode:

[0044] First layer composite: Prepare an aqueous solution of tin chloride (SnCl4) containing 10g / 100ml of tin and an aqueous solution of Ti chloride (TiCl 3) containing 10g / 100ml, take 100ml of each of the above aqueous solutions and add ethanol to form a 300ml first mixed solution. Immerse the modified titanium substrate in the obtained first mixed solution for 1 hour, dry it at 100°C in an atmospheric atmosphere for 10 minutes, transfer it to a muffle furnace and bake it at 600°C in an atmospheric atmosphere for 30 minutes. The above-mentioned immersion, drying, and baking processes are carried out in sequence until the first mixed solution is completely used up, and a layer containing a mixed oxide of tin (SnO2) and titanium (TiO2) is formed on the surface of the titanium substrate to obtain a titanium substrate containing a first composite layer.

[0045] Second layer composite: Prepare an aqueous solution containing 1g / 100ml of Ta chloride (TaCl 5) and an aqueous solution containing 10g / 100ml of Ti chloride (TiCl 3), take 100ml of each of the above aqueous solutions and ethanol to form a 300ml mixed solution. Immerse the titanium substrate that has passed the first composite layer in the obtained second mixed solution for 1 hour, dry it at 100°C in an atmospheric atmosphere for 10 minutes, transfer it to a muffle furnace and bake it at 600°C in an atmospheric atmosphere for 30 minutes. The above-mentioned immersion, drying and baking are carried out in sequence until the second mixed solution is completely used up, and a second layer containing a mixed oxide of tantalum (Ta2O5) and titanium (TiO2) is formed on the surface of the titanium substrate, and a titanium substrate anode electrode containing a second composite layer is obtained. The composition of the titanium substrate surface coating layer formed is TiO2-SnO2-Ta2O5, and the proportion of metal content is 69.3% Ti, 27.9% Sn, and 2.8% Ta.

[0046] Example 2

[0047] Preparation of titanium substrate anode for electrolysis of tetramethylammonium hydroxide

[0048] 2.1. Pretreatment of titanium substrate: A commercially available titanium substrate of length 8 cm × width 4 cm × thickness 2.0 mm was immersed in a 2 mol / L sodium hydroxide solution at 25°C for 20 minutes and then treated with acetone for 10 minutes to obtain a titanium substrate from which oil and grease had been removed; then, the substrate was immersed in a 0.5 mol / L oxalic acid solution at 45°C for 90 minutes to obtain a titanium substrate from which the oxide layer and grease had been removed.

[0049] 2.2. Surface modification of titanium substrate:

[0050] Immerse the titanium substrate with the oxide layer and grease removed in 100 ml of anhydrous ethanol solution with a titanium chloride concentration of 2 mol / L and a urea concentration of 2.0 mol / L. Slowly add 20 ml of deionized water within 20 minutes. After stirring evenly, transfer to a high-temperature and high-pressure reactor with a Teflon liner for hydrothermal reaction at 200°C for 12 hours. After the reaction is completed, naturally cool to room temperature and wash the titanium substrate with distilled water several times; place the titanium substrate with white powder on the surface in a drying oven at 120°C for 4 hours to obtain a titanium substrate with surface modified with titanium dioxide. Scrape a small amount of surface powder for sample testing. The XRD diffraction spectrum is shown as follows Figure 2 As shown, the XRD diffraction peaks show that the obtained surface white powder is a titanium dioxide phase.

[0051] 2.3. Preparation of composite anode electrode:

[0052] First layer composite: Prepare an aqueous solution of tin chloride (SnCl4) containing 10g / 100ml of tin and an aqueous solution of Ti chloride (TiCl 3) containing 10g / 100ml, take 100ml of each of the above aqueous solutions and add ethanol to form a 300ml first mixed solution. Immerse the modified titanium substrate in the obtained first mixed solution for 1 hour, dry it at 100°C in an atmospheric atmosphere for 10 minutes, transfer it to a muffle furnace and bake it at 600°C in an atmospheric atmosphere for 30 minutes. The above-mentioned immersion, drying, and baking are carried out in sequence until the first mixed solution is completely used up, and a layer containing tin and titanium mixed oxides is formed on the surface of the titanium substrate to obtain a titanium substrate containing a first composite layer.

[0053] Second layer composite: Prepare an aqueous solution containing 1g / 100ml of Ta chloride (TaCl 5) and an aqueous solution containing 10g / 100ml of Ti chloride (TiCl 3), take 100ml of each of the above aqueous solutions and ethanol to form a 300ml mixed solution. Immerse the titanium substrate that has passed the first composite layer in the obtained second mixed solution for 1 hour, dry it at 100°C in an atmospheric atmosphere for 10 minutes, transfer it to a muffle furnace and bake it at 600°C in an atmospheric atmosphere for 30 minutes. The above-mentioned immersion, drying and baking are carried out in sequence until the second mixed solution is completely used up, and a second layer containing tantalum and titanium mixed oxides is formed on the surface of the titanium substrate to obtain a titanium substrate anode electrode containing a second composite layer. The composition of the titanium substrate surface coating layer formed is TiO2-SnO2-Ta2O5, and the proportion of metal content is 72.9% Ti, 24.6% Sn, and 2.5% Ta.

[0054] Example 3

[0055] Preparation of titanium substrate anode for electrolysis of tetramethylammonium hydroxide

[0056] 3.1. Pretreatment of titanium substrate: A commercially available titanium substrate of length 8 cm × width 4 cm × thickness 2.0 mm was immersed in a 2 mol / L sodium hydroxide solution at 25°C for 20 minutes and then treated with acetone for 10 minutes to obtain a titanium substrate from which oil and grease had been removed; then, the substrate was immersed in a 0.5 mol / L oxalic acid solution at 45°C for 90 minutes to obtain a titanium substrate from which the oxide layer and grease had been removed.

[0057] 3.2. Surface modification of titanium substrate:

[0058] Immerse the titanium substrate with the oxide layer and grease removed in 100 ml of anhydrous ethanol solution with a titanium trichloride concentration of 1 mol / L and a urea concentration of 1.5 mol / L. Slowly add 20 ml of deionized water within 20 minutes, stir evenly, and transfer to a high-temperature and high-pressure reactor with a Teflon liner for hydrothermal reaction at 200°C for 12 hours. After the reaction is completed, naturally cool to room temperature and wash the titanium substrate with distilled water several times; place the titanium substrate with white powder on the surface in a drying oven at 120°C and dry for 4 hours to obtain a titanium substrate with surface modified with titanium dioxide. Scrape a small amount of surface powder for sample testing. The XRD diffraction spectrum is shown as follows Figure 2 As shown, the XRD diffraction peaks show that the obtained surface white powder is a titanium dioxide phase.

[0059] 3.3. Preparation of composite anode electrode:

[0060] First layer composite: Prepare an aqueous solution of tin chloride (SnCl4) containing 15g / 100ml of tin and an aqueous solution of Ti chloride (TiCl 3) containing 15g / 100ml, take 100ml of each of the above aqueous solutions and add ethanol to form a 300ml first mixed solution. Immerse the modified titanium substrate in the obtained first mixed solution for 1 hour, dry it at 100°C in an atmospheric atmosphere for 10 minutes, transfer it to a muffle furnace and bake it at 600°C in an atmospheric atmosphere for 30 minutes. The above-mentioned immersion, drying, and baking are carried out in sequence until the first mixed solution is completely used up, and a layer containing tin and titanium mixed oxides is formed on the surface of the titanium substrate to obtain a titanium substrate containing the first composite layer.

[0061] Second layer composite: Prepare an aqueous solution containing 2g / 100ml of Ta chloride (TaCl 5) and an aqueous solution containing 15g / 100ml of Ti chloride (TiCl 3), take 100ml of each of the above aqueous solutions and ethanol to form a 300ml mixed solution. Immerse the titanium substrate that has passed the first composite layer in the obtained second mixed solution for 1 hour, dry it at 100°C in an atmospheric atmosphere for 10 minutes, transfer it to a muffle furnace and bake it at 600°C in an atmospheric atmosphere for 30 minutes. The above-mentioned immersion, drying and baking are carried out in sequence until the second mixed solution is completely used up, and a second layer containing tantalum and titanium mixed oxides is formed on the surface of the titanium substrate, and a titanium substrate anode electrode containing a second composite layer is obtained. The composition of the titanium substrate surface coating layer formed is TiO2-SnO2-Ta2O5, and the proportion of metal content is 67.2% Ti, 28.9% Sn, and 3.9% Ta.

[0062] Comparative Example 1

[0063] Preparation of titanium substrate anode for electrolysis of tetramethylammonium hydroxide

[0064] 1. Pretreatment of titanium substrate: A commercially available titanium substrate of length 8 cm × width 4 cm × thickness 2.0 mm was immersed in a 2 mol / L sodium hydroxide solution at 25°C for 20 minutes and then treated with acetone for 10 minutes to obtain a titanium substrate from which oil and grease were removed; then, the substrate was immersed in a 0.5 mol / L oxalic acid solution at 45°C for 90 minutes to obtain a titanium substrate from which the oxide layer and grease were removed.

[0065] 2. Surface modification of titanium substrate:

[0066] The titanium substrate with the oxide layer and grease removed was immersed in 100 ml of ethanol solution containing 4.8 g of commercially available titanium dioxide, stirred evenly, and then transferred to a high-temperature and high-pressure reactor with a Teflon liner for hydrothermal reaction at 200°C for 12 hours. After the reaction was completed, it was naturally cooled to room temperature and the titanium substrate was washed with distilled water several times; the titanium substrate with white powder on the surface was placed in a drying oven at 120°C for 4 hours to obtain a titanium substrate with surface modified with titanium dioxide. A small amount of surface powder was scraped for sample testing, and the scanning electron microscope image is as follows Figure 3 The XRD diffraction spectrum is shown in Figure 2 As shown, the XRD diffraction peaks show that the obtained surface white powder is a titanium dioxide phase, and the microstructure is irregular granular.

[0067] 3. Preparation of composite anode electrode:

[0068] First layer composite: Prepare an aqueous solution of tin chloride (SnCl4) containing 10g / 100ml of tin and an aqueous solution of Ti chloride (TiCl 3) containing 10g / 100ml of Ti, take 100ml of each of the above aqueous solutions and add ethanol to form a 300ml first mixed solution. Immerse the modified titanium substrate in the obtained first mixed solution for 1 hour, dry it at 100°C in an atmospheric atmosphere for 10 minutes, transfer it to a muffle furnace and bake it at 600°C in an atmospheric atmosphere for 30 minutes. The above-mentioned immersion, drying, and baking are carried out in sequence until the first mixed solution is completely used up, and a layer containing a mixed oxide of tin (SnO2) and titanium (TiO2) is formed on the surface of the titanium substrate to obtain a titanium substrate containing a first composite layer.

[0069] Second layer composite: Prepare an aqueous solution containing 1g / 100ml of Ta chloride (TaCl 5) and an aqueous solution containing 10g / 100ml of Ti chloride (TiCl 3), take 100ml of each of the above aqueous solutions and ethanol to form a 300ml mixed solution. Immerse the titanium substrate that has passed the first composite layer in the obtained second mixed solution for 1 hour, dry it at 100°C in an atmospheric atmosphere for 10 minutes, transfer it to a muffle furnace and bake it at 600°C in an atmospheric atmosphere for 30 minutes. The above-mentioned immersion, drying and baking are carried out in sequence until the second mixed solution is completely used up, and a second layer containing a mixed oxide of tantalum (Ta2O5) and titanium (TiO2) is formed on the surface of the titanium substrate, and a titanium substrate anode electrode containing a second composite layer is obtained. The composition of the titanium substrate surface coating layer formed is TiO2-SnO2-Ta2O5, and the proportion of metal content is 69.2% Ti, 27.9% Sn, and 2.9% Ta.

[0070] Comparative Example 2

[0071] The method of Example 1 is adopted, except that the aqueous solution of the first composite layer contains only 10g / 100ml of tin chloride (SnCl4). The composition of the titanium substrate surface coating layer formed is TiO2-SnO2-Ta2O5, and the proportion of metal content is 57.3% Ti, 38.7% Sn, and 4.0% Ta.

[0072] Comparative Example 3

[0073] The method of Example 1 is adopted, except that the aqueous solution of the second composite layer contains only 1g / 100ml of Ta chloride (TaCl 5). The composition of the titanium substrate surface coating layer formed is TiO2-SnO2-Ta2O5, and the proportion of metal content is 57.3% Ti, 38.7% Sn, and 4.0% Ta.

[0074] Comparative Example 4

[0075] The method of Example 1 is adopted, except that the aqueous solution of the second composite layer contains only 10g / 100ml of Ti chloride (TiCl 3). The composition of the titanium substrate surface coating layer formed is TiO2-SnO2, and the ratio of metal content is 71.3% Ti and 28.7% Sn.

[0076] Comparative Example 5

[0077] The method of Example 1 is adopted, except that the aqueous solution of the first composite layer contains only 10g / 100ml of Ti chloride (TiCl 3). The composition of the titanium substrate surface coating layer formed is TiO2-Ta2O5, and the ratio is 96.0% Ti and 4.0% Ta in terms of metal content.

[0078] Comparative Example 6

[0079] The method of the above embodiment 1 is adopted, except that:

[0080] First layer composite: Prepare an aqueous solution of tin chloride (SnCl4) containing 10g / 100ml of tin and an aqueous solution of Ti chloride (TiCl 3) containing 10g / 100ml, take 100ml of each of the above aqueous solutions and add ethanol to form a 300ml first mixed solution. Immerse the modified titanium substrate in the obtained first mixed solution for 1 hour, dry it at 100°C for 10 minutes in an atmospheric atmosphere, and perform the above immersion and drying processes in sequence until the first mixed solution is completely used up, and transfer it to a muffle furnace and bake it at 600°C for 30 minutes in an atmospheric atmosphere. A layer containing a mixed oxide of tin (SnO2) and titanium (TiO2) is formed on the surface of the titanium substrate to obtain a titanium substrate containing a first composite layer.

[0081] Second layer composite: Prepare an aqueous solution containing 1g / 100ml of Ta chloride (TaCl 5) and an aqueous solution containing 10g / 100ml of Ti chloride (TiCl 3), take 100ml of each of the above aqueous solutions and ethanol to form a 300ml mixed solution. Immerse the titanium substrate that has passed the first composite layer in the obtained second mixed solution for 1 hour, dry it at 100°C in an atmospheric atmosphere for 10 minutes, and perform the above immersion and drying processes in sequence until the first mixed solution is completely used up, transfer it to a muffle furnace and bake it at 600°C in an atmospheric atmosphere for 30 minutes. A second layer containing a mixed oxide of tantalum (Ta2O5) and titanium (TiO2) is formed on the surface of the titanium substrate to obtain a titanium substrate anode electrode containing a second composite layer. The composition of the titanium substrate surface coating layer formed is TiO2-SnO2-Ta2O5, and the proportion of metal content is 69.3% Ti, 27.9% Sn, and 2.8% Ta.

[0082] Electrolysis experiment of titanium substrate anode electrode of the present invention

[0083] Pretreatment of F4402 cation exchange membrane: Before use, soak it in a 0.6 mol / L deionized sulfuric acid solution for 8 hours, rinse it with deionized water, then soak it in a 4 wt % tetramethylammonium hydroxide solution for 24 hours, rinse it with deionized water and set it aside.

[0084] In a double-chamber single-membrane electrolyzer, the composite titanium substrate obtained in the present invention is used as an anode, and a commercially available 304 stainless steel plate of 8 cm × 4 cm × 2.0 mm is used as a cathode electrode. 500 mL of a tetramethylammonium bicarbonate aqueous solution with a mass concentration of 18% is added to the anode chamber of the electrolyzer, and 500 mL of a tetramethylammonium hydroxide (TMAH) aqueous solution with a mass concentration of 2% is added to the cathode chamber; the electrolyzer temperature is maintained at 45 ° C, the voltage is 8 V, the current is 1.5 A, and the electrolysis is performed for 12 hours to obtain a semiconductor-grade TMAH aqueous solution in the cathode chamber. The content of metal ions (K, Ca, Na, Mg) (in ppb) is detected using inductively coupled plasma mass spectrometry (ICP-MS, GB / T37403-2019), and the mass concentration of the tetramethylammonium hydroxide aqueous solution is determined by hydrochloric acid titration, and the results are shown in Table 1.

[0085] Table 1 Electrolysis test results of Examples 1-3 and Comparative Examples 1-6

[0086]

[0087] Application of the electrode of the present invention in electrolyzing tetramethylammonium hydroxide (TMAH) aqueous solution

[0088] Weigh 100 grams of the tetramethylammonium hydroxide (TMAH) aqueous solution prepared in the embodiment, and add the corresponding alkaline substance, surfactant, alcohol and ether derivatives to prepare a developer. The alkaline substance is selected from one or more of choline, alcohol amine, amide, and pyrrolidone, and the added amount is based on the tetramethylammonium hydroxide (TMAH) aqueous solution, and the mass concentration is 0.5-3%. If the surfactant is a nonionic surfactant, examples include polyoxyethylene alkyl ether, polyoxyethylene polyoxypropylene alkyl ether, polyoxyethylene alkyl phenyl ether, polyoxyalkylene polycyclic phenyl ether, polyoxyethylene polyoxypropylene polyoxyethylene alkyl ether, polyoxypropylene polyoxyethylene polyoxypropylene alkyl ether, polyoxyethylene polyoxypropylene alkyl ether, polyoxyethylene polyoxypropylene alkyl phenyl ether, polyethylene glycol, polyoxyethylene polyoxypropylene glycol, polypropylene glycol, polyoxyethylene polyoxypropylene polyoxyethylene glycol, polyoxyethylene fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene alkyl amide, polyoxyethylene polyoxypropylene alkyl amide, alkylamino polyoxyethylene ether, alkylamino polyoxyethylene polyoxypropylene ether, acetylene glycol polyoxyethylene ether, coconut amine polyoxyethylene ether, and polyoxyethylene glycerol ether; the added amount is based on a tetramethylammonium hydroxide (TMAH) aqueous solution, and the mass concentration is 0.5-5%. The alcohol and ether derivatives include pentaerythritol, neopentyl glycol, xylitol, n-butanol, maltitol, ethylene glycol ether, and propylene glycol ether, and the added amount is based on the tetramethylammonium hydroxide (TMAH) aqueous solution, with a mass concentration of 0.5-3%. Other additives include anti-aging agents, defoamers, and corrosion inhibitors, with a content of 0.1-2%.

[0089] Preparation method of developer: prepare developer according to the formulation in Table 2, weigh 100 g of tetramethylammonium hydroxide (TMAH) aqueous solution electrolyzed at the cathode in Example 1, add corresponding alkaline substances, surfactants, alcohols and ether derivatives in sequence, optionally add additives, stir and mix thoroughly, and the mass content of the corresponding components is based on the amount of the electrolyzed aqueous solution.

[0090]

[0091] Performance evaluation of the prepared developer:

[0092] 1 Surface tension test method: The surface tension of the compositions of different concentrations was measured at room temperature using a BZY-2 surface tension meter by a platinum plate method. The experimental data are shown in Table 2 (the average value of three times was taken, and the error between two consecutive measurements was no more than 0.5 mN / m).

[0093] 2 Metal content test method: In accordance with GB / T37403-2019, the metal content in the developer is detected by inductively coupled plasma mass spectrometry.

[0094] 3 Operating temperature range: Take 10mL of the developer solution from the application example, heat it slowly while stirring, observe the temperature when the developer solution becomes turbid, then slowly cool the beaker, and read the temperature when the developer solution becomes clear. After averaging the turbid temperature and the clear temperature, make the following evaluation criteria based on the following temperatures:

[0095] √: Above 50℃, wide temperature range;

[0096] ○: 30 ~ 50℃, moderate temperature range;

[0097] ×: Below 30°C, the temperature range is narrow.

[0098] 4 Alkalinity stability test: Take the developer solution of the application example in air at room temperature and test the pH value change.

[0099] The above 1-4 performance evaluation test results are shown in Table 3.

[0100] Table 3 Performance evaluation of developer

[0101]

[0102] The present invention directly uses a tetramethylammonium hydroxide (TMAH) aqueous solution of cathode electrolysis as a component of the developer, and the developer composition obtained by adding additives has a lower surface tension, and because the metal content in the aqueous solution prepared by using a specific electrode is reduced, the metal content in the obtained developer is also low, and the metal content in all application examples is less than 3ppb, with an operating temperature range of 》=50°C, a wider applicable temperature, and more environmentally friendly and safe; Application Examples 1-4 and Application Example 7 have a smaller loss of alkalinity after storage for 5 days, and Application Examples 5-6 have a lower alkalinity than other application examples on the basis of not adding choline and diethanolamine, and the alkalinity loss is larger, and the addition of choline and diethanolamine can increase the pH and significantly improve the ability to maintain the pH alkalinity, so that the alkalinity is more stable and durable, and can be stored for a long time, with long-term alkalinity. In Application Example 7, since no alcohol or ether substances are added, its surface tension is increased even in the presence of a surfactant. The high-concentration cathode electrolysis aqueous solution using Example 3 of the present invention has a higher alkalinity and a stronger ability to maintain the alkalinity.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A low surface tension long-acting developer, characterized in that: The developer comprises a semiconductor-grade TMAH aqueous solution; The preparation process of the semiconductor-grade TMAH aqueous solution is as follows: before use, the F4402 cation exchange membrane is placed in a 0.6 mol / L sulfuric acid deionized water solution and soaked for 8 hours, washed with deionized water, and then soaked in a 4 wt% tetramethylammonium hydroxide aqueous solution for 24 hours, washed with deionized water and then used; a composite anode electrode for semiconductor-grade TMAH electrolysis is used in a double-chamber single-membrane electrolyzer, a commercially available 304 stainless steel plate of 8 cm×4 cm wide×2.0 mm thick is used as a cathode electrode, 500 mL of a tetramethylammonium bicarbonate aqueous solution with a mass concentration of 18% is added into the anode chamber of the electrolyzer, and 500 mL of a tetramethylammonium hydroxide aqueous solution with a mass concentration of 2% is added into the cathode chamber; the electrolyzer temperature is maintained at 45° C., the voltage is 8 V, the current is 1.5 A, and electrolysis is performed for 12 hours to obtain a semiconductor-grade TMAH aqueous solution in the cathode chamber; The method for preparing the semiconductor-grade composite anode electrode for TMAH electrolysis comprises the following steps: Step 1 Pretreatment of the titanium substrate: a commercially available titanium substrate of length 8 cm×width 4 cm×thickness 2.0 mm is subjected to degreasing and defatting treatments using alkali solution, acetone and acid solution in sequence to obtain a titanium substrate after degreasing and defatting; Step 2: Surface modification of titanium substrate: immerse the titanium substrate obtained in step 1 in 100 ml of anhydrous ethanol solution with a titanium trichloride concentration of 1-3 mol / L and a urea concentration of 0.5-3 mol / L, slowly drop 10-20 ml of deionized water within 20 minutes, stir evenly and transfer to a high-temperature and high-pressure reactor with a Teflon liner for hydrothermal reaction at 160-220°C for 6-12 hours; after the reaction is completed, naturally cool to room temperature, wash the obtained titanium substrate with distilled water several times; place the obtained titanium substrate with a white powder layer on the surface in a drying oven at 100-120°C for 2-4 hours to obtain a titanium dioxide-modified titanium substrate with a surface grid morphology structure; Step 3 Preparation of composite anode electrode: composite the first layer and composite the second layer on the surface of the titanium substrate modified with surface titanium dioxide obtained in step 2; First layer composite: prepare a SnCl4 aqueous solution containing 5-20g / 100ml and a TiCl3 aqueous solution containing 5-20g / 100ml, take 100ml of each of the aqueous solutions and ethanol to form a 300ml first mixed solution; immerse the titanium substrate modified with titanium dioxide in the first mixed solution for 0.5-2 hours, remove it, dry it at 80-120°C for 10-30 minutes in an atmospheric atmosphere, transfer it to a muffle furnace and roast it at 480-600°C for 30-240 minutes in an atmospheric atmosphere; carry out the above-mentioned immersion, drying and roasting processes in sequence until the first mixed solution is completely used up, and form a layer containing tin and titanium mixed oxides on the surface of the titanium substrate to obtain a titanium substrate anode electrode containing a first composite layer; Second layer composite: prepare a TaCl5 aqueous solution containing 1-6g / 100ml and a TiCl3 aqueous solution containing 5-20g / 100ml, take 100ml of each of the above aqueous solutions and ethanol to form a second mixed solution of 300ml; immerse the titanium substrate anode electrode obtained by the first layer composite in the obtained second mixed solution for 0.5-2 hours, then remove it, dry it at 80-120°C for 10-30 minutes in an atmospheric atmosphere, transfer it to a muffle furnace and roast it at 450-600°C for 30-240 minutes in an atmospheric atmosphere; carry out the above-mentioned immersion, drying and roasting processes in sequence until the second mixed solution is completely used up, and form a second layer containing tantalum and titanium mixed oxides on the surface of the titanium substrate to obtain a semiconductor-grade composite anode electrode for TMAH electrolysis.

2. The low surface tension long-acting developer according to claim 1, characterized in that: In the pretreatment process of step 1, the specific treatment method is to soak the titanium substrate in a 1-4 mol / L sodium hydroxide aqueous solution at 25°C for 10-60 minutes and then treat it with acetone for 10-30 minutes to obtain a deoiled and degreased titanium substrate; then soak it in a 0.5-2 mol / L oxalic acid aqueous solution at 45°C for 30-90 minutes.

3. The low surface tension long-acting developer according to claim 1, characterized in that: In step 3, during the first composite layer process, the concentration of the SnCl4 aqueous solution is 10-15 g / 100 ml, and the concentration of the TiCl3 aqueous solution is 10-15 g / 100 ml; in the second composite layer, the concentration of the TaCl5 aqueous solution is 1-2 g / 100 ml, and the concentration of the TiCl3 aqueous solution is 10-15 g / 100 ml.

4. The low surface tension long-acting developer according to claim 1, characterized in that: The developer is also added with alkaline substances, surfactants, alcohols and ether derivatives; the alkaline substance is selected as choline or a combination of choline and diethanolamine, the added amount is based on the amount of TMAH aqueous solution, and the mass concentration is 0.5-3%; the surfactant includes nonylphenol polyoxyethylene ether, and also includes one or two of coconut amine polyoxyethylene ether and polyoxyethylene glycerol ether, the added amount is based on the amount of TMAH aqueous solution, and the mass concentration is 0.5-5%; the alcohol and ether derivatives are selected from one or more of propylene glycol butyl ether and maltitol, the added amount is based on the amount of TMAH aqueous solution, and the mass concentration is 0.5-3%.

5. The low surface tension long-acting developer according to claim 4, characterized in that: The amount of the surfactant added is based on the amount of the TMAH aqueous solution, and the mass concentration is 0.5-2%.

6. The low surface tension long-acting developer according to claim 4, characterized in that: The added amount of the alcohol and ether derivatives is based on the amount of TMAH aqueous solution, and the mass concentration is 0.5-2%.

7. A low surface tension long-acting developer according to any one of claims 4 to 6, characterized in that: Anti-aging agent, defoaming agent and corrosion inhibitor are also added, and the added amount is based on the amount of TMAH aqueous solution, and the mass concentration is 0.1-2%; the anti-aging agent is one or more of amines and phenols, the defoaming agent is one or more of silicone oils, and the corrosion inhibitor is one or more of benzotriazole and 5-methylbenzimidazole.

Citation Information

Patent Citations

  • Composite developing solution for photo-etching

    CN103197516A

  • Tetramethylammonium hydroxide developing solution as well as preparation method and application thereof

    CN114859677A

  • Electrolysis electrode and method for producing aqueous quaternary ammonium hydroxide solution using such electrolysis electrode

    CN101027430A

  • Developing solution and method for production of finely patterned material

    CN101641647A